Los costos del contrato juvenil en las Empresas Industriales del Ecuador. - Quispe Fernandez, Gabith Miriam; Sánchez, Fernando; Arellano Cepeda, Otto Eulogio (Universidad Técnica de Machala, 2019)
The labor juvenile insertion is a challenge for the Ecuadoran companies, since he supposes an investment in human resources that eventually produce economic benefits. In this context, the investigation has the aim to determine the costs of insertion to the juvenile work between 18 and 26 years, in the industrial companies of the Ecuador, inside the frame of the Organic Law for the promotion of the juvenile work, exceptional regulation of the day of work, unemployment and insurance of unemployment, published in the Official Record 720, 28-III-2016. The deductive method is used, treats itself about an empirical study - descriptively. The study of case is applied to the Company FAIRIS C.A. located in Ambato's city. The results of the investigation demonstrate that the juvenile contracting in the industrial companies manages to increase the economic benefits; the costs of juvenile contracting are minor with relation to the costs of personnel with experience. Concluding, that the companies acquire significantly benefits for the juvenile contractings because the labor costs are minor and the labor performance is high.
La inserción laboral juvenil es un reto para las empresas ecuatorianas, ya que supone una inversión en recursos humanos que a la larga producen beneficios económicos. En ese contexto, la investigación tiene el objetivo de determinar los costos de inserción al trabajo juvenil entre 18 y 26 años, en las empresas industriales del Ecuador, dentro del marco de la Ley Orgánica para la promoción del trabajo juvenil, regulación excepcional de la jornada de trabajo, cesantía y seguro de desempleo, publicado en el Registro Oficial 720, 28-III-2016. Se usa el método deductivo, se trata de un estudio empírico - descriptivo. Se aplica el estudio de caso a la Empresa FAIRIS C.A. ubicado en la ciudad de Ambato. Los resultados de la investigación demuestran que la contratación juvenil en las empresas industriales logra incrementar los beneficios económicos; los costos de contratación juvenil son menores con relación a los costos de personal con experiencia. Concluyéndose, que las empresas adquieren significativamente beneficios por las contrataciones juveniles porque los costos laborales son menores y el rendimiento laboral es alto.
Keywords: COSTOS DE CONTRATACIÓN LABORAL; BENEFICIOS; RENDIMIENTO LABORAL